Broad Impairment of Natural Killer Cells From Operationally Tolerant Kidney Transplanted Patients - Dugast, Emilie; David, Gaëlle; Oger, Romain; Danger, Richard; Judor, Jean-Paul; Gagne, Katia; Chesneau, Mélanie; Degauque, Nicolas; Soulillou, Jean-Paul; Paul, Pascale; Picard, Christophe; Guerif, Pierrick; et al. (Frontiers in Immunology, 2017)
The role of natural killer (NK) cells in organ transplantation is controversial. This study aims to decipher their role in kidney transplant tolerance in humans. Previous studies highlighted several modulated genes involved in NK cell biology in blood from spontaneously operationally tolerant patients (drug-free kidney-transplanted recipients with stable graft function). We performed a phenotypic, functional, and genetic characterization of NK cells from these patients compared to kidney-transplanted patients with stable graft function under immunosuppression and healthy volunteers. Both operationally tolerant and stable patients harbored defective expression of the NKp46 activator receptor and lytic molecules perforin and granzyme compared to healthy volunteers. Surprisingly, NK cells from operationally tolerant patients also displayed decreased expression of the CD16 activating marker (in the CD56DimNK cell subset). This decrease was associated with impairment of their functional capacities upon stimulation, as shown by lower interferon gamma (IFNγ) production and CD107a membranous expression in a reverse antibody-dependent cellular cytotoxicity (ADCC) assay, spontaneous lysis assays, and lower target cell lysis in the 51Cr release assay compared to healthy volunteers. Conversely, despite impaired K562 cell lysis in the 51Cr release assay, patients with stable graft function harbored a normal reverse ADCC and even increased amounts of IFNγ+NK cells in the spontaneous lysis assay. Altogether, the strong impairment of the phenotype and functional cytotoxic capacities of NK cells in operationally tolerant patients may accord with the establishment of a pro-tolerogenic environment, despite remaining highly activated after transplantation in patients with stable graft function.